Oxissulfetos e oxissulfatos de térbio III produzidos a partir dos sulfato e sulfonato de térbio III: caracterização espectroscópica e estudo termoanalítico sob diferentes atmosferas - Rodrigues, Rodrigo Vieira (2012)
The purpose of this study is to synthesize the hydrated sulphate of Terbium III (using the oxide) and sulfonate ion through the same Diphenyl-4-Amine Sodium Sulfonate. These compounds were analyzed for their stability, characterized through the techniques of infrared spectroscopy, elemental analysis CHNS, X ray diffraction by the powder method, thermal analysis (DTA / DTG) and differential scanning calorimetry (DSC). IR spectra for both Sulfate and Sulfonate show significant changes due to linking groups, while residues of analysis ATG / DTG (O2 and H2: Ar/N2, CO) of the precursors have been allocated, according to DRX, the oxissulfetos Tb2OS2 and oxissulfatos Tb2O(SO4)2 of Tb3+. The interest of this comparison is to show that from the sulfate becomes is possible to obtain its own waste as oxidissulfite [Tb2OS2], dioxissulfite [Tb2O2S], oxidissulfate [Tb2O(SO4)2], dioxissulfate [TbO2SO4] and Tb3+ oxide [Tb2O3], while that from the restring in sulfonate to obtain dioxissulfite [Tb2O2S], dioxissulfate [TbO2SO4] oxide and Tb3+ [Tb2O3]. The influence of physical and chemical characteristics of the organic binder is a key part in this differentiation